2023
DOI: 10.7717/peerj.14754
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Saccharothrix algeriensis NRRL B-24137 to suppress Fusarium oxysporum f.sp. vasinfectum induced wilt disease in cotton

Abstract: Fusarium cotton wilt is a devastating disease of the cotton crop throughout the world, caused by Fusarium oxysporum f.sp. vasinfectum (FOV). Chemical control has many side effects, so, biological controls have been widely used for the management of Fusarium wilt. This study aimed to investigate the possible use of an actinomycetes Saccharothrix algeriensis (SA) NRRL B-24137 to control FOV. To access in-vitro anti-Fusarium ability of SA NRRL B-24137, dual culture assay, spore germination and seed germination te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Subsequently, the potential of the actinomycete SA as a biological control against FOV was explored. Their research included in vitro tests and greenhouse pot experiments, which demonstrated substantial anti-Fusarium activity and a reduction in disease incidence, suggesting the effectiveness of SA NRRL B-24137 in disease management [54]. Li and colleagues [55] investigated the role of salicylic acid (SA) as a biofungicide against Fusarium wilt.…”
Section: Enhancing Plant Defense Mechanismsmentioning
confidence: 99%
“…Subsequently, the potential of the actinomycete SA as a biological control against FOV was explored. Their research included in vitro tests and greenhouse pot experiments, which demonstrated substantial anti-Fusarium activity and a reduction in disease incidence, suggesting the effectiveness of SA NRRL B-24137 in disease management [54]. Li and colleagues [55] investigated the role of salicylic acid (SA) as a biofungicide against Fusarium wilt.…”
Section: Enhancing Plant Defense Mechanismsmentioning
confidence: 99%
“…vasinfectum (FOV) is an important disease affecting agents, nearly all cottongrowing regions of the world, and reduced cotton yield to intolerable levels (Seo et al, 2020). Many other species of Fusarium are also linked with roots of cotton but their role as pathogen is still not clear (Asif et al, 2023). FOV morphologically identical pathogenic, nonpathogenic and even beneficial strains.…”
Section: Introductionmentioning
confidence: 99%